ANALISIS PROFIL DAN SALURAN PEMASARAN INDUSTRI TAHU KARYA MANDIRI DI KELURAHAN ANAIWOI, KECAMATAN TANGGETADA, KOLAKA - Sulhija; Jusma Sri Putri; Nurmaya Aprilia; Indra Wijayanto; Hasbiadi; Prihantini, Campina Illa (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2021)
Tofu is a cheap staple food for people who are rich in nutritional content and relatively cheap purchasing power and of course all levels of society can consume it or buy it. Of course, tofu has been recognized by several neighboring countries, not only Indonesia, including Malaysia and Japan. In Anaiwoi Village, Tanggetada Subdistrict, a business was established with its production using soybeans as basic ingredients. Soybeans are used only to produce tofu and do not produce tempeh. The main objective of this study is to identify the home industry of “Karya Mandiri” tofu and tempeh through the identification of business profiles and marketing channels.